2010
DOI: 10.1089/ars.2009.2598
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Turnover and Aging of Long-Lived Postmitotic Cells: The Mitochondrial–Lysosomal Axis Theory of Aging

Abstract: It is now generally accepted that aging and eventual death of multicellular organisms is to a large extent related to macromolecular damage by mitochondrially produced reactive oxygen species, mostly affecting long-lived postmitotic cells, such as neurons and cardiac myocytes. These cells are rarely or not at all replaced during life and can be as old as the whole organism. The inherent inability of autophagy and other cellular-degradation mechanisms to remove damaged structures completely results in the progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
391
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 427 publications
(408 citation statements)
references
References 263 publications
(288 reference statements)
10
391
0
7
Order By: Relevance
“…The lysosomal hydrolases are then activated when they release the MP receptors that are recirculated to the Golgi apparatus. Finally, the late endosomes mature to lysosomes that lack MP receptors, are rich in acid hydrolases, have a pH of 4-5, and contain material to be degraded (Terman et al, 2010).…”
Section: The Role Of Lysosomes In Intracellular Iron Metabolismmentioning
confidence: 99%
See 3 more Smart Citations
“…The lysosomal hydrolases are then activated when they release the MP receptors that are recirculated to the Golgi apparatus. Finally, the late endosomes mature to lysosomes that lack MP receptors, are rich in acid hydrolases, have a pH of 4-5, and contain material to be degraded (Terman et al, 2010).…”
Section: The Role Of Lysosomes In Intracellular Iron Metabolismmentioning
confidence: 99%
“…acridine orange or other available lysotrackers, it was found that after heavy oxidative stress some lysosomes always remain intact, while even low oxidative stress results in the rupture of a small but obviously very sensitive population of lysosomes (Nilsson et al, 1997). The explanation for this phenomenon is probably that some lysosomes are actively engaged in degradation of iron-containg macromolecules, while resting lysosomes may contain little or none of this transition metal (Terman et al, 2010).…”
Section: Lysosomal Iron and Ionizing Irradiationmentioning
confidence: 99%
See 2 more Smart Citations
“…This morphology has been demonstrated to increase metabolic demands and the risk of oxidative stress in A9 cells compared to other dopaminergic cell populations (128)(129)(130). Long axons require more energy to accommodate transport machinery to and from soma, while the low diameter impairs motility and further increases the metabolic demands (131,132). Further, lack of nodes of Ranvier elevates Na + /K + activity due to a less efficient action potential mechanism (133).…”
Section: Selective Vulnerability Of Dopaminergic Neurons In the Snpc:mentioning
confidence: 99%